Ab initio calculation of vibrational frequencies of AsO glass - Rosli, A.N.; Zabidi, N.A.; Abu Kassim, H.; Shrivastava, K.N. (Elsevier, 2010)
We have used the density-functional theory to make models containing arsenic and oxygen atoms. The structures are optimized for the minimum energy of the Schrodinger equation. In this way, we obtain the bond distances and angles of the stable structures. We obtain the vibrational frequencies of each cluster. The calculated vibrational frequencies are compared with those found in the experimental Raman spectra. The values of the vibrational frequencies calculated for AsO(2:)ASO(4)(T(d))(:)AsO(2) (rectangular), AsO(2) (triangular) and AsO(3) (pyramidal) agree with those found in the Raman spectra of vitreous aresenic oxide, indicating that these clusters are really present in the arsenic oxide glass. (C) 2009 Elsevier B.V. All rights reserved.